Resistance & Sensitivity of the Microorganisms Isolated in 268 Patients of Loghman Hakim Teaching Hospital 2002 - Z Khosravi; Z Aminzadeh (Tehran University of Medical Sciences, 2005)
Background: Resistance to antibiotic agents is a world- wide problem, based on some reports from different hospitals. Susceptibility and resistant pattern of microorganisms in hospitals is important for manage and treatment of hospital acquired infections. This study was designed to determined susceptibility and resistant pattern of isolated microorganisms in Loghman Hakim hospital. Methods: The research method was descriptive and its technique was observational in three month of spring of 2002 over the 268 patients that have been refer to loghman hakim hospital and for different reasons need to have specimen culture (blood, urine, sputum, ulcer, abscess, CSF, etc). Blood agar and Macconkey agar for blood culture, Chocolate and Blood agar and Macconkey agar for CSF and other specimen cultures have been used. Results: The most common culture- positive was from Poisoning ward and endotracheal tube samples. The most common microorganism was Escherichia coli (E.coli) (60, 19%) and klebesilla (54, 17%) respectively. Maximum resistance of E.coli observed to Co-trimoxazol (71.6%), Ampicillin (84.3%), Cephazolin (83.7%) and Maximum resistance of klebesiella reported to Co-trimoxazol (72.6%), Ampicillin (96.1%), Cefazolin (76.7%). High resistance rate of microorganisms such as E.coli, klebsiella and Pseudomonas to antimicrobials such as Co-trimaoxazol, Aminoglicosides and first generation cephalosprins and increasing of Oxacillin-Resistance Staphylococci coagulase negative may be resulted from over use of these antibiotic agents. Conclusion: Early beginning and inappropriate dosage of antibiotic agents may be associated with an increased likelihood of the development of multiresistant bacteria,. So it is highly recommended to prohibit unnecessary prescription of antibiotics.